2017
DOI: 10.20319/lijhls.2017.32.5164
|View full text |Cite
|
Sign up to set email alerts
|

The Fear of Labor and the Roles of Midwives

Abstract: Pregnancy is a period in which women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…[20] In the literature, it was reported that fear of birth affecting the decision to have a Cesarean section was caused by lack of trust in the health personnel assisting the delivery, complications related to pregnancy, labor pain, negative thoughts about birth, loss of control over the birth and possible situations beyond the woman's control. [3,27,31] It is recommended that pregnant women, especially those who plan to have a normal delivery, are informed during antenatal education about the method and process of delivery, to increase confidence in healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…[20] In the literature, it was reported that fear of birth affecting the decision to have a Cesarean section was caused by lack of trust in the health personnel assisting the delivery, complications related to pregnancy, labor pain, negative thoughts about birth, loss of control over the birth and possible situations beyond the woman's control. [3,27,31] It is recommended that pregnant women, especially those who plan to have a normal delivery, are informed during antenatal education about the method and process of delivery, to increase confidence in healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%